PENANAMAN KARAKTER MANDIRI MELALUI DISCOVERY LEARNING PADA PEMBELAJARAN BAHASA INGGRIS KELAS V DI SDN SUDIMARA 07 CILEDUG - Fitria Rosmi; Nur'azizah, Mina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low level of independence of students in learning English, this can be seen from the confidence of students in completing English tasks. Therefore, this study aims to determine how the development of independent character through Discovery Learning in English learning Class V at Sdn Sudimara 07 ciledug. The research method used is descriptive qualitative conducted at Sdn Sudimara 07 Ciledug. The instruments used in this research are observation, interview, and documentation. Data collection was done by interviewing each subject. Technical data analysis using data triangulation. Subjects include English teachers and students of Grade V SDN Sudimara 07 ciledug. This research was conducted at Sdn Sudimara 07 Ciledug in semester 1 of the 2024-2025 academic year. The results of this study indicate that the application of Discovery Learning Methods in English learning can increase the independence of students in learning. Students become more active in finding additional information and are able to independently solve their tasks.